Influence of Scientifical and Technological Achievements on the Development of Housing Policy - Melnikienė, Rasa (Ekonomika, 1999)
Under market conditions, knowledge of the personal needs allows to rationalise the human economical activities that is directed towards the satisfaction of human personal needs, as well as the better resource usage. It is necessary to evaluate the changes of the needs when forming the priorities of the state socialeconomical policy. During this century, it was managed to apply the scientifical and technological achievements in the dwelling sector, so the dwelling needs has experienced some essential qualitative changes. The dwelling electrification, provision with water supply, the application of central heating system to the dwelling houses and other inventions has shaped the new qualitative dwelling parameters. Many states all around the world follow these parameters in implementation of dwelling policy. The purpose of this article is to evaluate the dwelling policy implementation in Lithuania from the standpoint of stock of dwellings quality improvement.